Mechanisms of resistance of desensitized enterobacteria to carbapenems isolated in a public reference laboratory in the State of Piauí, Brazil (Research, Society and Development, 2020)
Objective: Bacterial resistance refers to the ability of bacteria not to react to appropriate antibiotics used to eradicate them. Such fact occurs mainly due to mutations in bacterial genes, these occur at random, however, accelerated with incorrect use of antibiotic therapy. The production of Klebsiella pneumoniae carbapenemase (KPC) is an emerging example and its spread among enterobacteric variants already occurs in our country. Thus, we sought to analyze the percentage of contamination of the bacterium according to age and sex, its percentage of resistance through antibiogram analysis as well as mechanisms of resistance related to enterobacteria desensitized to Carbapenemic isolated in a public reference laboratory in Teresina-PI. Methodology: The sample was composed by collecting patients who presented positive results for enterobacteria and confirmed resistance to Carbapenemics through antibiogram. Data related to infection were collected by means of a questionnaire to fill out data. Results: Through the RT-PCR technique and obtaining the sociodemographic profile results, the predominance of K.pneumoniae bacteria was observed in female patients. It should also be noted that the study evidenced the frequency of genes 46% of the bla KPC gene that confers resistance to a wide range of antimicrobial agents.Conclusion: Based on the results obtained, we verified the genotypic frequency related to mechanisms of resistance to Rbapenemics using the RT-PCR technique. When assessing the sociodemographic data, it was possible to conclude that the highest frequency of KPC gene was 56% female, all of them testing positive for Klebsiella pneumoniae.